(untitled) (Research, Society and Development, 2019)
This paper aims to present and discuss an experience report, under the discipline of Internship in Social Spaces, of the Pedagogy course of the Franciscan University (UFN), based on the qualitative approach and the autobiographical method (JOSSO, 2004). The internship took place in the Riograndense Association of Equine Therapy and Equilibrium known as Hippos Equoterapia and unfolded in two moments: a) attendance to a practitioner with Down Syndrome (SD), in which he worked with activities related to Portuguese, mathematics and psychomotricity within the context of equine therapy, and b) cataloging of the educational and pedagogical games of Hippos Equoterapia, being carried out based on the System of Classification of Games and Toys (CUNHA, 2007). Therefore, it is concluded that the activities proposed to the practitioner with SD had positive effects. Regarding the cataloging of games, it is important to provide an organizational culture in the institution. Thus, it is evident the important role that the pedagogue has in non-formal education institutions.